Music as a chariot the evolutionary origins of theatre in time, sound, and music - Thomas, Richard K. 1953- (New York Routledge, 2018)
Music as a Chariot offers a multidisciplinary perspective whose primary proposition is that theatre is a type of music. Understanding how music enables the theatre experience helps to shape our entire approach to the performing arts. Beginning with a discussion on the origin and nature of time, the author takes us on an evolutionary journey to discover how music, language and mimesis co-evolved, eventually coming together to produce the complex way we experience theatre. The book integrates the evolutionary neuroscience of the human brain into this journey, offering practical implications and applications for the auditory expression of this concept--namely the fundamental techniques artists use to create sound scores for theatre. With contributions from directors, playwrights, actors and designers, Music as a Chariot explores the use of music to carry ideas into the human soul--a concept that extends beyond the theatrical to include film, video gaming, dance, or anywhere art is manipulated in time.
Chapter 1: Introduction: Why this Book -- Part I: The Nature of Time -- Chapter 2: Let There Be a Big Bang -- Chapter 3: The Great Mystery of Time -- Part II: Music = Time Manipulated -- Chapter 4: What Is Music? -- Chapter 5: Primate Numbers -- Part III: Song = Music + Idea -- Chapter 6: Campfire Songs (Rhythm and Entrainment) -- Chapter 7: Music and Language -- Chapter 8: Consonance and Dissonance (The Evolution of Line) -- Part IV: Theatre = Song + Mimesis -- Chapter 9: Ritual, Arousal, Reward, Ecstasy -- Chapter 10: Music, Mimesis, Memory -- Chapter 11: The Bronze Age and the Invention of Writing -- Chapter 12: Conclusion: Evolution and Greek Theatre.
"Focal Press book."
Includes bibliographical references.
Keywords: Music in the theater; Theaters -- Sound effects; Music -- Philosophy and aesthetics